Analisis Faktor-Faktor yang Memengaruhi Leverage dan Profitabilitas Perusahaan - Matsaid Budi Reksono; Teddy Chandra; Rini Yayuk Priyati (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
A firm’s leverage and profitability are two significant aspects of overall firm management. This study mainly aims at examining and analyzing the determinants of leverage and profitability in Indonesian mining firms listed by including both trade-off theory and pecking order theory approaches. Secondary data as sample has been collected for 26 Indonesian mining firms listed in Indonesian stock exchange (IDX), for the period of 9 years from 2010 to 2018. Firm’s size, asset tangibility, asset growth, and liquidity have been selected as exogenous variables to examine their effect on endogenous variables, i.e., leverage and profitability. Path analysis technique was employed to analyze the research data. The results indicate that leverage exerts negative impact on firm profitability. The finding results of this study provides great insights for Indonesian mining firm management, to integrate the financial leverage models in their financial decision to obtain optimum firm profitability.